2018
DOI: 10.1126/sciadv.aap8060
|View full text |Cite
|
Sign up to set email alerts
|

Organic fertilizer as a vehicle for the entry of microplastic into the environment

Abstract: Organic fertilizer from recycled biowaste was identified as a vehicle for entry of microplastic particles into the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
303
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 785 publications
(317 citation statements)
references
References 27 publications
3
303
1
10
Order By: Relevance
“…Nizzetto et al () estimated that the amount of microplastics added to European and North American soils via such applications exceeds the global burden now present in oceanic surface waters. Weithmann et al () observed that composts derived from household and commercial sources contained up to 895 microplastics kg −1 . The smallest microplastics examined by these authors were 1,000 μm, so the actual abundances were likely much higher.…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
“…Nizzetto et al () estimated that the amount of microplastics added to European and North American soils via such applications exceeds the global burden now present in oceanic surface waters. Weithmann et al () observed that composts derived from household and commercial sources contained up to 895 microplastics kg −1 . The smallest microplastics examined by these authors were 1,000 μm, so the actual abundances were likely much higher.…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
“…In addition to these almost 13 million metric tons of direct plastic contaminants that enter the environment each year [34], the usually durable commodity polymers also undergo incomplete disintegration caused by ultraviolet (UV) radiation, mechanical abrasion, and biological degradation [35]. This process produces microplastic polymer particles (MPPs), which are <5 mm fragments (fibres and spheres) resulting from their incomplete degradation (Figure 4), causing direct harm by their bioaccumulation and also indirect harm due to the toxic additives and microorganisms they carry on their large surface areas, which enter the food web and consequently, human food [36,37]. [30] with permission from The Royal Society of Chemistry.…”
Section: Sustainability and Safety Assessmentmentioning
confidence: 99%
“…In a study on macro-and microplastics in agricultural soil, up to 205 macroplastic pieces per hectare (ha) and 0.34 ± 0.36 MPs pieces per kilogram soil (dry weight) were detected; illustrating the vast extent of soil contamination [11]. Entry routes of MPs into terrestrial systems are not well known; however, initial studies have attempted to elucidate these possible pathways, such as, for example, via the use of organic fertilizers as a vehicle for MP entry [12,13].…”
Section: Introductionmentioning
confidence: 99%